The Effect of Prebiotics to The Ammonia Value from Tilapia Culture (Oreochromis niloticus - Kristina Aditya Putra; Saifullah Saifullah; Achmad Noerkhaerin Putra (Jurnal Perikanan dan Kelautan, 2016)
Tilapia (Oreochromis niloticus) is a freshwater commodity with high economicvalue. To increase the production of tilapia, intensive culture needs to be byfeeding quality and water quality. This study aimed to effect of prebioticssupplementation to tilapia fed on ammonia value. This experiment consisted offour treatments with three replications. The treatments were A (prebiotics 0%), B(prebiotics 1%), C (prebiotics 2%) and D (prebiotics 3%). The results showedthat lowest ammonia value indicated in the treatment of prebiotic 2% of 0,0000.Prebiotic subsequent treatment of 3% 0.0001, prebiotic treatment 1% 0.0002, andthe highest value in the treatment of ammonia prebiotic 0% of 0.0006.Supplementation of 2% prebiotics is the best treatment because it showed thelowest ammonia value than the other treatments